Studi Komparatif Pola Penciptaan Manusia Dalam Kejadian 1:26-28 Dengan Teori Evolusi Darwin - Susanto, Viki (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2025)
In this article, the author tries to conduct a comparative study of the pattern of human creation in Genesis 1:26-28 with Darwin's theory of evolution. According to Genesis 1:26-28, humans are God's creations formed from dust and soil, then given the breath of life. Meanwhile, according to Darwin's theory, humans are the result of the evolution of other living creatures, starting from very simple organisms that then changed into what they are today. The research method used by the author is qualitative research using literature studies on views from various journals, articles, Bibles and books. The results of this study show that there are fundamental differences regarding the origin of humans. Theologians hold the belief that the first humans were created through God's special work. While evolutionary followers argue that humans are a change in form from other organisms over a very long period of time. Through this research, it is hoped that it will provide additional views in the treasury of scientific knowledge and can be used as one of the considerations to answer the differences in views that are still being discussed today.